"Causes Of Unemployment in the Modern Economy and Ways to Eliminate it" (Zien Journal of Social Sciences and Humanities, 2022)
This article analyzes the causes, factors, and measures to combat unemployment, which is one of the most pressing issues in each country, and how important they are